The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/ccd.24601
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound‐guided systematic two‐stent techniques for coronary bifurcation lesions and reduced late stent thrombosis

Abstract: The IVUS-guided two-stent technique was associated with significantly reduced late stent thrombosis, with a resultant reduction in ST-elevation MI. © 2012 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…1 In the DES era, a meta-analysis including this trial and 10 registries reported that IVUS guidance may reduce ST and cardiac death after DES, although TVR rates were reduced only in complex lesion cohorts. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The present study reports by far the largest experience with IVUS guidance of DES implantation, with a major strength being enrollment of an all-comers population. In this population, IVUS guidance was associated with lower rates of ST, MI, and ischemia-driven TLR and TVR compared with angiography guidance alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the DES era, a meta-analysis including this trial and 10 registries reported that IVUS guidance may reduce ST and cardiac death after DES, although TVR rates were reduced only in complex lesion cohorts. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The present study reports by far the largest experience with IVUS guidance of DES implantation, with a major strength being enrollment of an all-comers population. In this population, IVUS guidance was associated with lower rates of ST, MI, and ischemia-driven TLR and TVR compared with angiography guidance alone.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Nonetheless, definitive randomized trials to demonstrate whether IVUS guidance improves clinical outcomes after stent implantation have not been performed, with most prior trials being underpowered and restricted to noncomplex lesions. The benefits of IVUS after drug-eluting stent (DES) use are particularly controversial given the improved outcomes with DES compared with bare metal stents.…”
mentioning
confidence: 99%
“…IVUS contributes to the assessment of complex bifurcation lesions, plaque burden and location, bifurcation angles, morphology of the carina, and ostial lesions [12][13][14][15]. Since IVUS guidance facilitates the lesion evaluation, the selection of an optimal device size, the full coverage of the lesion, and an accurate assessment of the treatment, it might lower the rates of TLR, death, stent thrombosis, and MI [12][13][14][15]. However, the complete IVUS guidance in the present study did not lead to prominent reduction of TLR compared to other previous studies in which the frequency of the IVUS guidance was low.…”
Section: Discussionmentioning
confidence: 99%
“…Since intravascular sound (IVUS) optimizes percutaneous coronary interventions (PCI), device selection, and lesion evaluation; it has been reported to lower the rates of death, myocardial infarction (MI), TLR, and stent thrombosis after the deployment of DES in bifurcation lesions [12][13][14][15]. However, in studies of bifurcation lesions including [200 patients, IVUS was actually performed in 15-40 % of patients [3][4][5]10].…”
Section: Introductionmentioning
confidence: 99%
“…2) [53][54][55]. A pullback wire technique might be the best practice to facilitate distal rewiring, and imaging devices such as IVUS or OCT may allow the confirmation of the site of re-wiring [50,53,54]. In addition, in case of re-wiring into MVafter implantation of SB stent in culotte technique, re-crossing the wire at the cell located close to the carina is also crucial to avoid unnecessary lengthening of new metallic carina, which may induce more flow disturbance and delayed endothelial coverage of the metallic carina (Fig.…”
Section: Optimizing 2-stenting Techniquesmentioning
confidence: 99%